Kaempferol From Penthorum chinense Pursh Attenuates Hepatic Ischemia/Reperfusion Injury by Suppressing Oxidative Stress and Inflammation Through Activation of the Nrf2/HO-1 Signaling Pathway - Chen, Yifan; Li, Tongxi; Tan, Peng; Shi, Hao; Cheng, Yonglang; Cai, Tianying; Bai, Junjie; Du, Yichao; Fu, Wenguang (Frontiers in Pharmacology, 2022)
Hepatic ischemia/reperfusion injury (HI/RI) is a common complication closely related to the prognosis of liver surgery, and effective prevention and treatment methods are still unavailable. Ischemia/reperfusion (I/R) injury is caused by tissue damage during ischemia and sustained oxidative stress and inflammation during reperfusion. Penthorum chinense Pursh is a traditional Chinese medicine widely used to treat liver disease since ancient times. Kaempferol (KAE), a highly purified flavonoid active monomer isolated and extracted from Penthorum chinense Pursh, was investigated for its protective effect on HI/RI. Our study indicates that KAE pretreatment alleviated I/R-induced transaminase elevation and pathological changes. Further analysis revealed that KAE pretreatment attenuates I/R-induced oxidative stress (as measured by MDA, GSH, and SOD levels) in vivo and reduces hypoxia/reoxygenation (H/R) -induced reactive oxygen species (ROS) generation in vitro. Meanwhile, KAE inhibited NF-κB activation and reduced the release of pro-inflammatory factors (TNF-α and IL-6) to protect the liver from I/R-induced inflammation. Nuclear erythroid 2-related factor 2 (Nrf2) is a key regulator of cytoprotection because it induces the expression of anti-inflammatory, antioxidant, and cytoprotective genes. Therefore, we analyzed the protein levels of Nrf2 and its downstream heme oxygenase-1 (HO-1) in the liver and hepatocytes of mice, respectively, and discovered that KAE pretreatment activated the Nrf2/HO-1 signaling pathway. In summary, this study confirmed the hepatoprotective effect of KAE on HI/RI, which inhibits oxidative stress and inflammation, by activating the Nrf2/HO-1 signaling pathway.